PENGARUH NEGATIF ETIKA DAN MORALITAS PERETAS ATAU HACKER DALAM UPAYA MEMBANGUN SUMBERDAYA MANUSIA YANG BERBASIS SCIENCE DAN TEKNOLOGI DI EXPLOID ID HACKER - M Asmar Maheri (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Education and Technology is one of the pillars of human development and nation. Therefore, the government of Indonesia made education and technology as one of the needs for the whole society, but along with the high influence of technology in today's many who abuse technology tersebut.Internet is one technology that can not be separated in the present, any information can be searched and which usually misuses the Internet is called Peretas. Hackers or hackers are people who study, analyze, modify, break into computers and computer networks, either for profit or motivated by challenges. On the other hand the academics are required to better in building competence and technology-based innovation. Of course, the implementation must also promote moral and ethics. It is intended that all can run in accordance with the norms that have been embedded in the people of Indonesia. This is in line with what Kemenristekdikti, Syahril Caniago delivered in a technology seminar entitled 'Application of Technology to Preparing Young Generation in National' held in Hall Hall of Tangerang Regency Regent on Saturday (7/1/17).